2012
DOI: 10.1111/j.1471-4159.2012.07771.x
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent blockade of free radical and microsomal prostaglandin E synthase‐1‐mediated PGE2 production improves safety and efficacy in a mouse model of amyotrophic lateral sclerosis

Abstract: J. Neurochem. (2012) 122, 952–961. Abstract While free radicals and inflammation constitute major routes of neuronal injury occurring in amyotrophic lateral sclerosis (ALS), neither antioxidants nor non‐steroidal anti‐inflammatory drugs have shown significant efficacy in human clinical trials. We examined the possibility that concurrent blockade of free radicals and prostaglandin E2 (PGE2)‐mediated inflammation might constitute a safe and effective therapeutic approach to ALS. We have developed 2‐hydroxy‐5‐[2‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 55 publications
(100 reference statements)
1
40
0
1
Order By: Relevance
“…9) Furthermore, inhibition of mPGES-1 by AAD-2004, a dual-function drug derived from aspirin and sulfasalazine, prevented the elevation of PGE2 content in the spinal cord of ALS model mice, and improved both motor function and survival. 10) These results suggest that PGE2 plays a pivotal role in the pathogenesis of ALS.…”
mentioning
confidence: 88%
“…9) Furthermore, inhibition of mPGES-1 by AAD-2004, a dual-function drug derived from aspirin and sulfasalazine, prevented the elevation of PGE2 content in the spinal cord of ALS model mice, and improved both motor function and survival. 10) These results suggest that PGE2 plays a pivotal role in the pathogenesis of ALS.…”
mentioning
confidence: 88%
“…Beginning from 10 months of age, Tg-βCTF99/B6 mice and their non-transgenic control mice were fed either lab chow containing AAD-2004 or no drug (control group). AAD-2004 was prepared as described previously [14] and was provided by GNT Pharma Inc. (Yongin, Korea). We prepared the lab chow containing AAD-2004 and control food.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, it was demonstrated that AAD-2004 had an anti-oxidant property in primary cortical culture, and its anti-oxidant capacity was similar to that by its analog neu2000 [13]. AAD-2004 reduced autophagosome formation, axonopathy, and motor neuron degeneration, improving motor function and increasing life span in in a mouse model of amyotrophic lateral sclerosis [14]. In the present study, we investigated whether AAD-2004 produces a beneficial effect against neuronal loss in the brain of Tg-βCTF99/B6 mice.…”
Section: Introductionmentioning
confidence: 99%
“…In SOD G93A transgenic mice, AAD-2004, 2-hydroxy-5-[2-(4-trifluoromethylphenyl)-ethylaminobenzoic acid] blocked free radical production and PGE 2 formation and inhibits mPGES1 and microglial activation in the spinal cord. As a consequence, AAD-2004 reduces auto-phagosome formation, axonopathy, and motor neuron degeneration, improving motor function and increasing life span [122]. These results suggest that mPGES-1 in motor neurons could play a role in the pathogenesis of ALS and that mPGES-1 could work sequentially in motor neurons and activated microglia to produce ALS symptoms in SOD G93A mice.…”
Section: The Non-genomic Role Of Vitamin D In Alsmentioning
confidence: 99%